Recognising workplace learning: the emerging practices of e-RPL and e-PR - Cameron, Roslyn (Emerald Group Publishing Limited, 2012)
Purpose: The use of e-portfolios in recognition of prior learning (RPL) processes in workplace and professional practice contexts has attracted little attention in the literature due to its emergent nature. This study seeks to explore the growing incidence of e-portfolio-based RPL (e-RPL) and professional recognition (e-PR) processes in Australia and the implications this has for recognising workplace learning. Design/methodology/approach: The paper utilises an exploratory study and involves a content analysis of a selected sample of data sources. The sample includes the abstracts and papers presented at the 2009 VET E-portfolios Showcase and the 2010 ePortfolios Australia conference and the Australian Flexible Learning Framework (AFLF) funded E-portfolio implementation trials 2009 and 2010. Findings: The paper finds an array of e-RPL and e-PR operationalised across multiple fields/disciplines and contexts. The incidence of e-PR is more dominant than that of e-RPL. The findings result in the development of a framework that provides the conceptual scaffolding for recognition systems in the workplace.Research limitations/implications: The study is limited to Australian based data sources. Further analysis could be expanded to international contexts to increase the data and evidence on e-RPL and e-PR processes and the implications these have for recognising workplace. The framework developed from the study provides a conceptual launch pad into future lines of inquiry which can critically explore the underlying pedagogies and knowledge paradigms which have dominated in formal learning systems. Practical implications: The paper includes implications for the correct matching of practices and tasks to appropriate types of e-portfolio based RPL and PR along a continuum of formal to informal learning and varying degrees of learner control. Originality/value: This paper presents an analytical framework for exploring e-RPL and e-PR as distinct processes of recognition through a synthesis of RPL and e-portfolio research and theoretical constructs. The framework includes a typology of e-RPL and e-PR based on Smith and Tillema's typology of portfolios and Cameron's models of RPL. The framework will assist in analysing recognition processes undertaken in workplace contexts